Integrated framework for quantity surveying practices for conservation projects / Umi Kalsum Zolkafli@Zulkifly - Zolkafli@Zulkifly, Umi Kalsum (Institute of Graduate Studies, UiTM, 2018)
Majority of heritage buildings in Malaysia are deteriorating. Previous researchers observed that the deterioration affecting the structural and fabric of the heritage buildings. Continuous care and protection are needed through conservation to limit the deterioration. Conserving heritage buildings are difficult because conservation projects are ambiguous, unique and cannot be duplicated. The scope of work, specification, duration or cost of conservation works cannot be accurately predetermined at early stage. The tender documents can be complicated and lack of critical information due to failure in exploiting the integrated heritage documents by quantity surveyors. Therefore, the aim of this study is to develop an integrated documentation framework to overcome ambiguities in improving quantity surveyors’ basic services in building conservation projects. This aim is achieved through the four following objectives; (1) to measure the level of ambiguities of building conservation projects; (2) to measure the level of performance of quantity surveyors’ basic services in building conservation projects; (3) to measure the level of integration of documentation used by quantity surveyors’ in building conservation projects and; (4) to establish relationships between ambiguities in building conservation projects’, integrated documentation and performance of quantity surveyors’ basic services. The study was conducted using mixed-method research design. For qualitative method, eight (8) registered quantity surveyors were interviewed using semi-structured interview and the data were analyzed using content and template analysis. For quantitative method, thirty six (36) questionnaires were analyzed using Software Package for Statistical Analysis and Partial Least Square of Structured Equation Modeling. The findings show that the variables with the highest level of ambiguity in conservation projects are the uniqueness of the building, the building technology and the complexity of the project. The result also revealed that the lowest quantity surveyors performances in basic services are in the ‘preparing bills of quantities and other tender documents’ and the ‘preparation of preliminary estimates and cost plans’. The thesis also found that the documents used by quantity surveyor are moderately integrated. The results also show that there are significant relationships between ambiguities in building conservation projects and quantity surveyors’ basic services. The integrated document is found to be partially mediating the ambiguities in building conservation project to the quantity surveyors basic services.